2015
DOI: 10.1002/mabi.201500243
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐Containing Multilayer Capsules by Templating on Mesoporous CaCO3 Particles: POST‐ and PRE‐Loading Approaches

Abstract: Encapsulation of model proteins (catalase, insulin, aprotinin) into multilayer dextran sulphate/protamin capsules by templating on CaCO3 microparticles is investigated employing: (i) PRE-loading into CaCO3 particles by adsorption or co-synthesis and (ii) POST-loading into performed capsules. Protein encapsulation is governed by both its size and electrostatic interactions with the carbonate microparticles and multilayer shell. PRE-loading enables improved encapsulation compared to POST-loading (catalase conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 65 publications
0
44
0
Order By: Relevance
“…This gives a very high efficiency of the loading, high protein content, and uniform distribution of the loaded protein molecules. 74,75 A number of various proteins such as aprotinin and insulin have been successfully loaded into crystals by ADS and COS. 74,75 The morphology of the crystals may affect the protein loading, 76 which is of high importance for pharmacological applications. 77 Although the potential for the utilization of crystals as carriers for protein loading is obvious, the loading mechanism through co-synthesis is poorly understood.…”
Section: -33mentioning
confidence: 99%
See 1 more Smart Citation
“…This gives a very high efficiency of the loading, high protein content, and uniform distribution of the loaded protein molecules. 74,75 A number of various proteins such as aprotinin and insulin have been successfully loaded into crystals by ADS and COS. 74,75 The morphology of the crystals may affect the protein loading, 76 which is of high importance for pharmacological applications. 77 Although the potential for the utilization of crystals as carriers for protein loading is obvious, the loading mechanism through co-synthesis is poorly understood.…”
Section: -33mentioning
confidence: 99%
“…74 Here, we have tested the retention of catalase activity after loading into CaCO 3 crystals by COS using a similar approach. Taking into account the maximum adsorption capacities found in this study, it was found that the maximum amount of active protein (after dissolution of the core with EDTA) for COS is 60.9 mg per 1 g of CaCO 3 crystals while encapsulation by ADS from a solution of the same protein concentration provides 27.7 mg of active catalase per 1 g of CaCO 3 crystals.…”
mentioning
confidence: 99%
“…The protein content in particles corresponded to the ratio of the protein amount to the weight of the dry preparation. The activity of aprotinin was measured by residual trypsin esterase activity using BAEE as a sub strate [30]; the measurements were performed after suspending particles in 0.1 M NaOH for 1 min and then diluting the solution with 0.5 M Tris buffer (1 : 10). The preservation of aprotinin activity was assessed by the ratio of the relative percentage of the active inhib itor in the particles to the similar value for the native protein taken in the same amount.…”
Section: Methodsmentioning
confidence: 99%
“…Different techniques and materials can be used for the preparation of polymer microcapsules, such as polymersomes [92], self-assembled vesicles [93], and LbL films [94,95]. Among them, LbL film-based microcapsules are currently widely used for the development of micro-containers for drug delivery because they are simple to prepare under mild conditions.…”
Section: Lbl Films Coated On the Surface Of Colloidal Particles And Nmentioning
confidence: 99%